1977
DOI: 10.3758/bf03209131
|View full text |Cite
|
Sign up to set email alerts
|

Shock intensity and warning signal effects on several measures of operant avoidance acquisition

Abstract: Acquisition of both signaled and unsignaled operant avoidance learning was studied in 64 rats as a function of shock intensity, with three different warning signals used in the signaled procedure. In both signaled and unsignaled avoidance, overall response rate was a progressively increasing function of shock intensity. This was due to both an absolute and relative increase in the frequency of responses at shorter interresponse times with increasing shock intensity. Presence of an effective warning signal in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

1978
1978
1985
1985

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 16 publications
(9 reference statements)
0
4
0
Order By: Relevance
“…Thisresult, however, may have been due to the use of a buzzer signal, because acoustic stimuli can be very effective as active avoidance CS (for differences between acoustic and visual signals in rat avoidance, see Biederman, 1967;Bolles, Hargrave, & Grossen, 1970;Frontali & Bignami, 1973, 1974Jacobs & LoLordo, 1977;Myers, 1964Myers, , 1977Rosie, Frontali, & Bignami, 1969;Schindler & Weiss, 1982;Whittleton, Kostanek, & Sawrey, 1965; for mice see Oliverio, 1967).…”
mentioning
confidence: 99%
“…Thisresult, however, may have been due to the use of a buzzer signal, because acoustic stimuli can be very effective as active avoidance CS (for differences between acoustic and visual signals in rat avoidance, see Biederman, 1967;Bolles, Hargrave, & Grossen, 1970;Frontali & Bignami, 1973, 1974Jacobs & LoLordo, 1977;Myers, 1964Myers, , 1977Rosie, Frontali, & Bignami, 1969;Schindler & Weiss, 1982;Whittleton, Kostanek, & Sawrey, 1965; for mice see Oliverio, 1967).…”
mentioning
confidence: 99%
“…That is, under the signaled procedure each group showed a substantial decrease in responding and an increase in both the absolute number and proportion of responses in the preshock period , in comparison to the unsignaled condition. Myers (1977) made the rather perplexing observation that avoidance response rate increased as shock intensity increased, but the probability of responding during the signal was unaffected by shock intensity. He proposed that a warning signal does acquire a discriminative function, which improves avoidance efficiency in terms of responses per shock received, but it also acquires to some degree a response-suppressive The absolute number of responses that occurred during the presignal vs. the signal period under the two avoidance procedures is shown in Figure 3 (even though no signal actually occurred during unsignaled avoidance).…”
Section: Avoidancementioning
confidence: 99%
“…These authors speculate that brief signals may induce freezing responses, which are incompatible with active avoidance. Myers (1964Myers ( , 1977 found that the type of warning signal employed had a major effect, with a buzzer resulting in much lower shock rates than a tone, a light, or no signal. It is intere sting to note that differences in shock rates between the latter groups were quite smalL Mean shock rates per hour were: buzzer , 10.8; tone, 21.5; light, 24.1; no signal, 27.0.…”
Section: Avoidancementioning
confidence: 99%
See 1 more Smart Citation